Turtle Island : foods and traditions of the indigenous peoples of North America - Sherman, Sean, 1974-; Nelson, Kate (Journalist); Donnelly, Kristin (Clarkson Potter, 2025)
"Discover the multifaceted story of the foods that have linked the environment, traditions, and legacy of Native American tribes for millenia through over 150 ancestral and modern Indigenous recipes from three-time James Beard Award-winning Sioux chef Sean Sherman. Sean Sherman, Oglala Lakota, is a leading figure in the Indigenous food movement-serving as the go-to source for stories on Indigenous food, Indigenous food issues, and recipes. In Turtle Island, he explores the diverse Native foodways of this continent, spotlighting the foods that have nourished, both physically and spiritually, the North American peoples for generations. Organized by regions, this book highlights the unique culinary traditions of Turtle Island-the name for this land across multiple Indigenous cultures-that are as varied and rich as the landscapes from which they arise. Learn to eat with the seasons, consume meat and fish nose-to-tail, focus on plant-forward dishes, and discover how to better feed yourself. These are truly delicious recipes to put today's nutrition-packed Indigenous pantry on your table, including: Wild-Rice Crusted Walleye Cakes Squash and Pepita Tartlets Wild Turkey and Mushroom Stew with Sassafras and Pine Broth Cedar Maple Baked Beans Summer Succotash Dried Venison and Corn Salad Great Lakes Granola, and much more Alongside the recipes, you'll meet inspiring Indigenous chefs and community leaders who are contributing to the revival of Indigenous food systems. Turtle Island features rich narrative essays that spotlight the people producing, gathering, and cooking these foods today, including remarkable stories of ingenuity and adaptation that capture the resilience of tribal communities. Turtle Island exemplifies how Native foodways can teach us all how to connect with the natural world around us, to embrace our differences, and to strive for a world that centers humanity and respect"-- Provided by publisher.